2007
DOI: 10.1086/522933
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Analysis of Mitochondrial DNA in Northern Asian Populations

Abstract: To elucidate the human colonization process of northern Asia and human dispersals to the Americas, a diverse subset of 71 mitochondrial DNA (mtDNA) lineages was chosen for complete genome sequencing from the collection of 1,432 control-region sequences sampled from 18 autochthonous populations of northern, central, eastern, and southwestern Asia. On the basis of complete mtDNA sequencing, we have revised the classification of haplogroups A, D2, G1, M7, and I; identified six new subhaplogroups (I4, N1e, G1c, M7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
218
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(239 citation statements)
references
References 66 publications
(139 reference statements)
11
218
1
9
Order By: Relevance
“…10,13,[31][32][33] In this connection, we consider challenging the assertion by Tamm et al 34 : 'A novel demographic scenario of relatively recent gene flow from Beringia to deep into western Siberia (Samoyed-speaking Selkups) is the most likely explanation for the phylogeography of haplogroup A2a, which is nested within an otherwise exclusively Native American A2 phylogeny'. The single Selkup mitogenome, attributed to A2a by Tamm et al, 34 indeed belongs to A2a1 (Supplementary Figure S1).…”
Section: New Findings and Interpretationmentioning
confidence: 76%
See 1 more Smart Citation
“…10,13,[31][32][33] In this connection, we consider challenging the assertion by Tamm et al 34 : 'A novel demographic scenario of relatively recent gene flow from Beringia to deep into western Siberia (Samoyed-speaking Selkups) is the most likely explanation for the phylogeography of haplogroup A2a, which is nested within an otherwise exclusively Native American A2 phylogeny'. The single Selkup mitogenome, attributed to A2a by Tamm et al, 34 indeed belongs to A2a1 (Supplementary Figure S1).…”
Section: New Findings and Interpretationmentioning
confidence: 76%
“…This conjecture is supported by the overlap of the Yukaghir, Tubalar, Altai-kizhi, Buryat, Tuvan, Chukchi, Naukan, and Canadian Eskimo (Inuit) mtDNA sequences within the D4b2a phylogeny. 10,13,31 The …”
Section: Haplogroup D4b1a2mentioning
confidence: 99%
“…43 The ages of the lineages G2a2 (further defined by mutation 16193 and named G2a2 tentatively) and M9a1a2a (characterized by mutations 16145, 16316 and a back mutation at site 16362, and designated as M9a1a2a) (Table 4) were estimated by using the r statistic 44,45 with the suggested calibration rates. 44,46 RESULTS AND DISCUSSION On the basis of the combined information from control-region and partial coding-region segments, the majority (96.34%; 237/246) of the Nepalese mtDNAs could unambiguously be allocated into the defined haplogroups of East Eurasian (36.59%; 90/246), 1,[20][21][22][23][24][25] Table S1, Supplementary Material online), 5 and this pattern remains almost stable for both the East Eurasian (45.11%; 189/419) and South Asian (47.49%; 199/419) components after taking into account the recently reported Nepalese mtDNA data. 5 As for the 21 samples with ambiguously phylogenetic status, completely sequencing their mtDNA genomes revealed that virtually all of these samples in fact belong to the already defined haplogroups, such as M3, M5, M18, M30, M35, M43, D4, R8 and M60.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, results of mtDNA analysis in northern Eurasian populations do not support a northern Asian migration route out of Africa, but they do predict that there were at least two migrations into South Siberia, one from East Asia and one from West Eurasia. 6 West Eurasian mtDNA haplogroups found in gene pools of South Siberians (for example, N1e, I4, J1b2, N1a, U4 and X2e) demonstrate an obvious link between populations of Siberia and those of West Asia, the Caucasus and East Europe. It is noteworthy that complete mtDNA genome-based coalescence times for haplogroups X2e, J1b2 and N1a suggest their postglacial flows (about 12-15 Ka) from the west.…”
Section: Introductionmentioning
confidence: 98%
“…1 This is consistent with results of mitochondrial DNA (mtDNA), and Y chromosome studies showing that North-Asian populations have a closer genetic relationship with Central Asian and West-Eurasian populations. [2][3][4][5][6][7] The presence of West-Eurasian genetic components in North and East Asia can be interpreted either as the evidence of ancient migration via the northern route 8 or simply as the reflection of recent population admixture. 9,10 However, results of mtDNA analysis in northern Eurasian populations do not support a northern Asian migration route out of Africa, but they do predict that there were at least two migrations into South Siberia, one from East Asia and one from West Eurasia.…”
Section: Introductionmentioning
confidence: 99%